Low seroprevalence of hepatitis delta virus co-infection in hepatitis B virus-infected blood donors in China: A multicenter study - Chang, Le; Yan, Ying; Ji, Huimin; Sun, Huizhen; Jiang, Xinyi; Lu, Zhuoqun; Wang, Lunan; Group, HBV-Infected Blood Donors Study (Frontiers in Microbiology, 2022)
Hepatitis delta virus (HDV) coinfected with HBV causes severe viral hepatitis, however, the number of HDV infection may be underestimated. In the present study, we enrolled 1,141,331 blood donations, routinely tested for HBsAg and/or HBV DNA, from 21 blood establishments in China. 2,690 donors were HBsAg and/or HBV DNA positive after screening tests. After verification of HBsAg and HBV DNA, 1,490 samples were HBsAg confirmed-positive, including 1,459 HBV DNA-positive samples, and 825 samples were seronegative but HBV DNA positive. We first analyzed demographic characteristics of involved 2690 donors with different HBV infection status and found the proportions of males, the older donors, workers and farmers were higher in HBsAg-/HBV DNA+ group. Then we evaluated specificity of HDV IgG and IgM antibody assays with 375 HBsAg and HBV DNA confirmed-negative samples, and 374 were tested negative using the two assays, respectively, suggesting a specificity of 99.73% for both assays (374/375, 95% Cl: 98.51–99.95%). Subsequently, we tested for HDV IgG and IgM of 2,315 HBsAg and/or HBV DNA confirmed-positive samples, and nine showed reactivity for IgG, while two were reactive for IgM. All these 11 reactive samples were tested again with another HDV pan-Ig and IgM testing assays and HDV RNA, and only one donor was identified as HDV IgG positive and HDV RNA negative, showing an HDV seroprevalence of 0.067% (95%CI: 0.012%-0.38%) among HBsAg-positive blood donors in China. The positive donor was followed up for two years after the donation date, and decreased antibody titer of HDV IgG and HBsAg conversion were observed, and the infection status of the donor was HDV infection with recovery and occult hepatitis B virus infection with genotype C2. These results indicated a low seroprevalence of HDV infection among blood donors and a low risk of HDV transmission through blood transfusion in China.